2016
DOI: 10.1080/17445647.2015.1124716
|View full text |Cite
|
Sign up to set email alerts
|

Geology of Monte Gallo (Palermo Mts, NW Sicily)

Abstract: The promontory of Monte Gallo (Palermo, NW Sicily) is a spectacular site where Upper TriassicEocene carbonate platform rocks and Quaternary continental to marine deposits are well exposed. A Mesozoic-Paleogene rock succession allows the potential visitor to easily detect the features and the evolution of the Panormide carbonate platform, a shallow-water paleogeographic domain of the Southern Tethyan margin. Quaternary deposits, as well many landforms, enable the visitor to directly identify the interplay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…As a result of a subsequent uplift event (during or shortly after the Sicilian stage) these blocks gradually emerged starting during the Middle Pleistocene stage, as indicated by the present-day stair-step flights of uplifted marine terraces of the MiddleUpper Pleistocene stages, which are located in the northern coastal plains up to about 100-300 m a.s.l. Based on the altitude of the inner edge of the MIS 5.5 and in agreement with the researchers who studied these coastal areas (Mauz et al 1997;Antonioli et al 1999Antonioli et al , 2006Di Maggio et al 1999;Scicchitano et al 2011;Giunta et al 2012;;Sulli et al 2013;Basilone & Di Maggio 2016) the average rate of the postTyrrhenian uplift is between about 0.032 -0.1 (NW coast) and 0.36 m/ky (NE coast). Generally, a few, large polycyclic coastal platforms overlooking the MIS 5.5 marine terrace developed where the uplift rate is less than 0.1 m/ky (e.g., Trapani and San Vito lo Capo areas); while successions of several orders of marine terraces consisting of smaller coastal platforms occurred where the uplift rate is higher than 0.1-0.15 m/ky (e.g., plain of Buonfornello; Sant'Agata di Militello area).…”
Section: Discussionsupporting
confidence: 64%
“…As a result of a subsequent uplift event (during or shortly after the Sicilian stage) these blocks gradually emerged starting during the Middle Pleistocene stage, as indicated by the present-day stair-step flights of uplifted marine terraces of the MiddleUpper Pleistocene stages, which are located in the northern coastal plains up to about 100-300 m a.s.l. Based on the altitude of the inner edge of the MIS 5.5 and in agreement with the researchers who studied these coastal areas (Mauz et al 1997;Antonioli et al 1999Antonioli et al , 2006Di Maggio et al 1999;Scicchitano et al 2011;Giunta et al 2012;;Sulli et al 2013;Basilone & Di Maggio 2016) the average rate of the postTyrrhenian uplift is between about 0.032 -0.1 (NW coast) and 0.36 m/ky (NE coast). Generally, a few, large polycyclic coastal platforms overlooking the MIS 5.5 marine terrace developed where the uplift rate is less than 0.1 m/ky (e.g., Trapani and San Vito lo Capo areas); while successions of several orders of marine terraces consisting of smaller coastal platforms occurred where the uplift rate is higher than 0.1-0.15 m/ky (e.g., plain of Buonfornello; Sant'Agata di Militello area).…”
Section: Discussionsupporting
confidence: 64%
“…Tectonic features (general term): Basilone and Di Maggio [14] suggested that the Monte Gallo geosite (Italy) boasted tectonic peculiarities. Panizza [7] noted that some key unique geological features representing in the geosites of the Dolomites (Italy) are tectonic.…”
Section: Experience-based Evidencementioning
confidence: 99%
“…The settlement rate of Dendropoma cristatum was surveyed in situ using limestone blocks (5 × 5x2 cm) as a substrate. This limestone belonged to the Marsala Synthem, a Lower Pleistocene marine/coastal deposit along the Palermo plain (Sicily) and was a cemented bioclastic calcarenite rich in invertebrate fossils, including vermetids (Di Maggio et al, 2009;Basilone and Di Maggio, 2016;Agate et al, 2017). Before running the settlement-choice experiment, freshly cut limestone blocks were autoclave sterilised and conditioned either by exposure to bacterial isolates in the laboratory or by exposure to natural conditions in the field.…”
Section: Limestone Block Preparationmentioning
confidence: 99%